Surgical myomectomy followed by oral Myfembree vs standard of care - Alkhrait, Samar; Al-Hendy, Ayman; Alkelani, Hiba; Karrison, Theodore; Laveaux, Obianuju Sandra Madueke (PloS one, 2024)
Uterine leiomyomas (often referred to as fibroids or myomas) are common benign, hormone-dependent tumors that grow in the uterus and occur in approximately 25% of reproductive age women, depending on selected population. Treatment recommendation is typically based on fibroid size, location, the patient's age, reproductive plans, and obstetrical history. Despite the range of treatment options available for uterine fibroids and their symptoms, including hysterectomy, myomectomy, endometrial ablation, endometrial uterine artery embolization, and magnetic resonance-guided focused-ultrasound surgery, myomectomy remains the gold standard treatment for patients who desire fertility-preserving surgery for their uterine fibroids. Myomectomy, while a prevalent surgical option for the removal of fibroids, carries known risks such as fibroid recurrence, symptom recurrence, and the subsequent need for reintervention. Despite ongoing research and advances in medical treatments for fibroids, there currently are no universally recommended therapeutic interventions proven to effectively delay the recurrence of fibroids or the return of symptoms following this procedure. This situation underscores a significant area of unmet medical need and highlights the importance of continued investigation into preventive strategies and long-term management options for patients undergoing fibroid removal with uterine preservation. We designed a study to assess the efficacy of the new FDA-approved GnRH antagonist, Myfembree in delaying the return of fibroids and their associated symptoms. A randomized, prospective, open-label clinical trial. The participants (n = 136) will be randomly distributed into two groups. The Control Group (Standard of care) will receive treatment with standard of care (SoC) after surgical myomectomy and the treatment group will receive Relugolix combination therapy (Myfembree®) after surgical myomectomy. The study protocol was approved by the University of Chicago's Institutional Review Board (IRB#22-0282), ensuring that all participants would provide written informed consent before their inclusion. In this project, we propose the use of daily dosed Relugolix combination therapy (Relugolix with estradiol and norethindrone acetate), which is approved for uterine fibroids treatment, has the potential to delay the recurrence of fibroid symptoms, prolong the improved quality of life and delay need for re-intervention after uterine sparing surgery.